A virtual reality based app to educate health care professionals and medical students about inflammatory arthritis: Feasibility study - Klemm, Philipp; Kleyer, Arnd; Tascilar, Koray; Schuster, Louis; Meinderink, Timo; Steiger, Florian; Lange, Uwe; Möller-Ladner, Ulf; Knitza, Johannes; Sewerin, Philipp; Mucke, Johanna; Pfeil, Alexander; et al. (JMIR Serious Games, 2021)
Background: Inflammatory arthritides (IA) such as rheumatoid arthritis or psoriatic arthritis are disorders that can be difficult to comprehend for health professionals and students in terms of the heterogeneity of clinical symptoms and pathologies. New didactic approaches using innovative technologies such as virtual reality (VR) apps could be helpful to demonstrate disease manifestations as well as joint pathologies in a more comprehensive manner. However, the potential of using a VR education concept in IA has not yet been evaluated. Objective: We evaluated the feasibility of a VR app to educate health care professionals and medical students about IA. Methods: We developed a VR app using data from IA patients as well as 2D and 3D-visualized pathological joints from X-ray and computed tomography generated images. This VR app (Rheumality) allows the user to interact with representative arthritic joint and bone pathologies of patients with IA. In a consensus meeting, an online questionnaire was designed to collect basic demographic data (age, sex); profession of the participants; and their feedback on the general impression, knowledge gain, and potential areas of application of the VR app. The VR app was subsequently tested and evaluated by health care professionals (physicians, researchers, and other professionals) and medical students at predefined events (two annual rheumatology conferences and academic teaching seminars at two sites in Germany). To explore associations between categorical variables, the ? 2 or Fisher test was used as appropriate. Two-sided P values =.05 were regarded as significant. Results: A total of 125 individuals participated in this study. Among them, 56% of the participants identified as female, 43% identified as male, and 1% identified as nonbinary; 59% of the participants were 18-30 years of age, 18% were 31-40 years old, 10% were 41-50 years old, 8% were 51-60 years old, and 5% were 61-70 years old. The participants (N=125) rated the VR app as excellent, with a mean rating of 9.0 (SD 1.2) out of 10, and many participants would recommend use of the app, with a mean recommendation score of 3.2 (SD 1.1) out of 4. A large majority (120/125, 96.0%) stated that the presentation of pathological bone formation improves understanding of the disease. We did not find any association between participant characteristics and evaluation of the VR experience or recommendation scores. Conclusions: The data show that IA-Targeting innovative teaching approaches based on VR technology are feasible.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Feasibility; Inflammatory arthritis; Psoriatic arthritis; Rheumatoid arthritis; Virtual reality